Polyfunkční dům - Dobeš, Josef (Vysoké učení technické v Brně. Fakulta stavební, 2023)
Práce řeší statický návrh vybraných částí nosné konstrukce. Obsahuje předběžný návrh, statickou analýzu v některém programovém systému pro výpočet konstrukcí, návrh a jejich posouzení.

The work deals with an alternative design of the selected parts of the load-bearing structure. It includes preliminary design, structural analysis in a structural analysis software system, design and their assessment.
Multifunctional house
Keywords: beton; železobeton; stropní deska; průvlak; schodiště; concrete; reinforced concrete; floor slab; beam; staircase